Управління ризиками та аналіз діяльності суб`єктів зовнішньоекономічної діяльності митними органами країн ЄС - Медвідь, Ю. О.; Medvid, Y. (КНТУ, 2015)
У статті розкрито особливості процесу управління митними ризиками в країнах ЄС. Визначено основні групи ризиків та основні групи показників діяльності суб’єктів зовнішньоекономічної діяльності (ЗЕД), що аналізуються митними органами. Встановлено, що сучасними тенденціями аналізу митних ризиків є моделювання ланцюга поставок товарів, дослідження інформації, що пов’язана з виявленими фактами неправомірності та фактами, що можуть свідчити про ймовірність недотримання митних правил. The article reveals peculiarities of customs risk management process in the EU in the aspect of analysis of foreign activities of economic entities. In particular, the process of customs risk management includes the following steps: establishing strategic, organizational and management principles, analysis and risk assessment, risk treatment, monitoring. The basis of the risk system is the analysis of risk indicators of foreign economic activity of entities. Among key indicators we can highlight the next: frequency and volume of declaration of goods by entities engaged in the foreign economic activities; dynamics of the ratio declaration of customs value and customs duties; declaration of goods, which belong to groups of products with significant differentiation of rates of duties or originate from countries with customs preferences; mode and route of goods delivery; the time interval and consistency of places of customs clearance; changing suppliers, country of origin, classification of goods by entities engaged in the foreign economic activities and others etc.
Risk management and analysis of the activities of foreign economic entities by customs authorities of the EU countries
Keywords: аналіз; зовнішньоекономічна діяльність; митний контроль; митні органи ЄС; управління ризиками; analysis; foreign trade; customs control; the customs authorities of the EU; risk management